Outcomes of Arterio-venous Fistula Reconstruction in Chronic Kidney Disease Patients Presenting in Tertiary Care Hospital in Eastern Nepal - Thakur, Dipak Kumar; Yadav, Ajay Kumar; Agrawal, Chandra Shekhar (Birat Journal of Health Sciences, 2022)
Introduction: Renal Replacement Therapy is the treatment modality for the chronic kidney disease (CKD) which ranges from hemodialysis, peritoneal dialysis to the renal transplantation, the latter being the best form of treatment. But, renal transplantation is available at limited centers only so hemodialysis is the most commonly used treatment modality of chronic kidney disease which requires a vascular access. But there are limited vascular surgeons in the region so most of the arterio-venous (AV) fistulas are reconstructed by Urologist/Surgeons exposed to vascular surgery during their residency/training period. Objectives: To know the factors influencing the site selection, to assess the success rate and to document the complications of AV fistula reconstruction. Methodology: This is a hospital based prospective observational study conducted in the Birat Medical College – Teaching Hospital, Morang, Nepal from June 2021 to May 2022. We included the CKD patients requiring vascular access for hemodialysis with Color Doppler available for vascular mapping. Patients with brachial sites previously used and without Color Doppler were excluded from the study. AVF was reconstructed under local anesthesia and outcomes were recorded. Results: Thirty one patients of CKD underwent AVF reconstruction over the study period. Male and female ratio was 1.33 (57% and 43%). The mean age was 42.14 ± 11.34 years (Range 26-65 years). The mean diameter of radial artery (RA) and cephalic vein (CV) at wrist were 1.92 ± 0.56mm and 1.91 ± 0.20 mm respectively. Similarly, the mean diameter of brachial artery (BA) and CV at elbow were 3.66 ± 0.87mm and 3.57 ± 0.55 mm respectively. The fistula reconstructed were Lt RC (radio-cephalic) – 50% (14), Lt BC (brachio-cephalic) -35.71% (10) and Lt BB ( brachio-basalic) - 14.29% (4) respectively. Complications occurred in 4 cases (14.28%). Conclusion: Selection of type of AVF creation is influenced by the vessel diameter as well as previous fistula surgery status and AVF access for hemodialysis has adequate patency with acceptable complications.